A case of a patient with type 1 diabetes mellitus and anorexia nervosa with changes to the central nervous system - Armand Bajaka (Kazimierz Wielki University, 2024)
Co-occurrence of anorexia nervosa (AN) and diabetes mellitus type 1 (T1DM) is an uncommon disease combination in clinical practice.  Treatment of T1DM may affect outcomes in AN patients due to self-modification of insulin dosage. In the presented case 14-year-old patient diagnosed with both T1DM and AN has been modifying her insulin-dependent treatment to prevent gaining weight. Undercontrolled glucose levels resulted in early-stage diabetic vascular complications in the central nervous system found in MRI.  Due to higher T1DM morbidity of eating disorders patients, adjustments and special control of insulin treatment and blood glucose levels as well as HbA1c should be maintained in the prevention of diabetic complications, especially in individuals with lower treatment compliance. As AN may lead to structural changes and a decrease in cognitive functions,  increased supervision of AN patients with T1DM can lower the risk of cumulative negative effects on the brain.